Excellent Service Quality of Land Administration in Response to The Community A Comparative Study of Kendal Regency and Semarang City - Salma, Lina; Fidiyani, Rini (JURNAL AKTA, 2025)
This study aims to analyze the quality of excellent land administration services based on community response in two regions with different characteristics, namely Kendal Regency and Semarang City. The main issue examined focuses on differences in community perceptions and experiences of public services in the land sector, particularly regarding the aspects of speed, transparency, and professionalism of officials. The approach used is qualitative with a comparative case study design, which allows researchers to explore social phenomena in depth in a local context. Data were collected through semi-structured interviews, participatory observation, and documentation studies, with participants selected using purposive and snowball sampling. The results of the study identified three main themes, namely: (1) public perceptions of excellent service, (2) responsiveness and professionalism of officials, and (3) transparency and certainty of services. The Kendal community considers the friendliness of officials to be a key aspect of service, but still faces obstacles in terms of certainty of time and cost. Meanwhile, the people of Semarang consider the efficiency and openness of the digital system to be the main advantages, despite the challenge of the digital literacy gap. These findings reinforce the SERVQUAL theory by adding the dimensions of socio-cultural context and service digitalization. Theoretically, this study contributes to the development of adaptive service-based public administration studies, while practically providing recommendations for improving the capacity of officials and integrating inclusive digital service systems. Further research is recommended to explore the aspects of inclusiveness and digital literacy in public services in semi-rural areas.